The sociolinguistics of digital Englishes - Friedrich, Patricia; Figueiredo, Eduardo H. Diniz de (Routledge, Taylor & Francis Group, 2016)
The Sociolinguistics of Digital Englishes introduces core areas of sociolinguistics and explores how each one has been transformed by the current era of digital communication and the Internet. This ground-breaking book demonstrates how key concepts such as language change, speech communities, gender construction and code-switching are affected by digital communications.